The effect of capital adequacy ratio and loan to deposit ratio on return on asset with non-performing loan as moderating variable in banking companies listed in BEI - Thomas Sumarsan Goh; Erika Erika; Henry Henry; Syawaluddin Syawaluddin (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2022)
This study aims to know the impact of capital adequacy and loan to deposit ratio on financial performance with credit risk as a moderating variable in the banking companies listed on the Indonesia Stock Exchange period of 2015 to 2019.We have 43 banking companies in population, and we take 23 companies as our samples. The data analysis model is an interaction method, usually referred to as Moderated Regression Analysis (MRA). The results show that capital adequacy has an impact on financial performance in banking companies listed on the Indonesia Stock Exchange from 2015 to 2019. The loan to deposit ratio does not effect financial performance. The existence of credit risk, as the moderating variable, will strengthen the relationship between capital adequacy and financial performance and the relationship between the loan to deposit ratio and financial performance. Also, the existence of credit risk as the moderating variable will strengthen capital adequacy and loan to deposit ratio on financial performance.